2021
DOI: 10.1016/j.molstruc.2020.129433
|View full text |Cite
|
Sign up to set email alerts
|

Anti-COVID-19 terpenoid from marine sources: A docking, admet and molecular dynamics study

Abstract: Highlights Screening more than fifty natural products for the SARS CoV-2 M pro protein target The compounds with higher hydrophobicity and lower flexibility can be more favorable inhibitor Terpenoid from marine sponge Cacospongia mycofijiensis shows excellent SARS CoV-2 M pro inhibitory activity In the point of binding affinity, bioav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 38 publications
1
39
0
3
Order By: Relevance
“…Similarly, a previously established binding mode for Lopinavir and Ritonavir against 3CL pro was obtained during our analysis which provides support for the binding mode of identified Hit compounds (Bolcato et al, 2020;. Recently, a terpenoid (T3) from marine sponge Cacospongia mycofijiensis was also identified through in silico studies against SARS CoV-2 3CL pro showing similar binding interactions like our hit molecules (Sepay et al, 2021). A recent pharmacophore-based study was published where authors screened the same MNP library against SARS-CoV-2 3CL pro (Gentile et al, 2020) and identified 17 different hits with different scaffolds.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, a previously established binding mode for Lopinavir and Ritonavir against 3CL pro was obtained during our analysis which provides support for the binding mode of identified Hit compounds (Bolcato et al, 2020;. Recently, a terpenoid (T3) from marine sponge Cacospongia mycofijiensis was also identified through in silico studies against SARS CoV-2 3CL pro showing similar binding interactions like our hit molecules (Sepay et al, 2021). A recent pharmacophore-based study was published where authors screened the same MNP library against SARS-CoV-2 3CL pro (Gentile et al, 2020) and identified 17 different hits with different scaffolds.…”
Section: Discussionsupporting
confidence: 84%
“…The top three phytoligands from each medicinal plants showing good binding affinity and interaction with the M pro and ACE2 were subjected to 25ns of MD simulation analysis using Gromacs 5.1.4 simulation package ( Sepay et al, 2020 ). The topology parameter files of the proteins were generated with GROMOS96 all force filed and the ligand topology file was generated using PRODRG2 web server.…”
Section: Methodsmentioning
confidence: 99%
“…Sulphated polysaccharides from marine microorganisms like sea cucumber Stichopus japonicus and Fucoidan from brown algae can have an excellent inhibitory effect on SARS-CoV-2 [184]. Recent reports revealed a T3 terpenoid isolated from marine sponge Cacospongia mycofinensis inhibits the action of Mpro via hydrogen bond interactions [185].…”
Section: Microbial Metabolites and Compounds From Marine Microorganisms Targeted Against Sars-cov-2mentioning
confidence: 99%